THE USE OF ENERGY EFFICIENT TECHNOLOGIES IN THE FRAMEWORK OF IMPLEMENTATION OF INVESTMENT PROJECT «ORGANIZATION OF PRODUCTION OF ROLLED BAR IRON WITH THE CONSTRUCTION OF SMALL-SECTION WIRE ROLLING MILL» OJSC «BSW – MANAGEMENT COMPANY OF HOLDING «BMC» - N. I. Anelkin; O. M. Kirilenko; V. E. Marushkevich; S. A. Mozgov (Литьë и металлургия)
This article reveals the main energy efficient solutions and innovations implemented in the framework of the investment project «Organization of production of rolled bar iron with the construction of small-section wire rolling mill» in the open joint stock company «Belarusian metallurgical works (BSW) – Management Company of Holding «Belarusian Metallurgical Company (BMC)». This project was included in the list of the most important projects for the creation of new enterprises and industries that are crucial for the innovative development of the Republic of Belarus. Supplier of technology and equipment for the project were made by the company Danieli & C. Officcine Meccaniche SpA (Italy). The modern and unique equipment used in this investment project allows to use more than 90% of fuel and energy resources (by using the heat recuperator of flue gases, heat recovery boiler, recuperative burners, etc.). Implementation of the project allowed to carry out the maximum processing of production and to receive new production with higher added value.